When and How Does Psychological Voice Climate Influence Individual Change Readiness? The Mediating Role of Normative Commitment and the Moderating Role of Work Engagement - Lee, Chun-Hsien; Wang, Mei-Ling; Liu, Min-Shi (Frontiers in Psychology, 2017)
This research explores the linking mechanisms and conditional processes underlying the relationship between psychological voice climate and individual change readiness. In accordance with the social identity theory, we argued that normative commitment would mediate the relationship between psychological voice climate and individual change readiness; furthermore, work engagement would moderate the proposed indirect effect. Two-wave survey data were collected from 187 full-time employees in a government-owned institute of research and development and were adopted for moderated mediation analysis. The results showed that normative commitment mediates the relationship between psychological voice climate and individual change readiness. Furthermore, work engagement strengthens the effect of psychological voice climate on individual change readiness in an indirect manner via normative commitment. Based on the findings, the theoretical implications and practical suggestions were discussed.